La Commission européenne et l'enseignement supérieur : une réforme au-delà de Bologne - Roser Cussó (Les éditions de la Maison des sciences de l'Homme, 2006)
The higher education reform proposed by the European Commission (EC) is more far-reaching than that undertaken in the Bologna process. In EC documents regarding the reform, the development of a system of quality assurance -an issue shared with the Bologna process- would lead to propositions for the social and institutional restructuring of universities. In other words, the new criteria and procedures of quality assurance could not only imply, in principle, a transformation of the conditions of knowledge production, but also involve a transformation of roles and responsibilities for the various actors in higher education. Lastly, according to the EC, the Bologna process should be, in the medium-term, integrated into broader programmes such as the Lisbon Strategy or lifelong learning.